Production performance and egg quality of quails (Coturnix japonica) during several periods of the day - Pizzolante, CC [UNESP]; Faltarone, ABG [UNESP]; Garcia, Edivaldo Antonio [UNESP]; Saldanha, ESPB [UNESP]; Deodato, AP [UNESP]; Sherer, MR [UNESP]; Mendes, AA [UNESP]; Mori, C [UNESP]; Pelicia, K [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
Three experiments were carried out to analyze the performance and egg quality of Japanese quails throughout the day when submitted to different lighting programs. In each experiment, birds were submitted to a period of 28 days for adaptation to the lighting program. During the following three days, each day - from 7 am to 7 pm or 9 pm - was divided into six or seven periods of two hours each, and the remaining hours corresponded to another single period. All birds were submitted to the same management practices, and received water and feed ad libitum. The experimental diet was formulated according to NRC (1994) standards. It was observed lower feed intake in the period of 9 pm to 7 am, and a higher incidence of lay from 3 pm to 7 pm, as opposite to hens, which peak of egg laying occurs during the morning. Some controversial results were found among experiments as to eggshell quality during the different periods of the day. Variation on the lighting program had little influence on the other performance and egg quality parameters.
Keywords: Periods of lay; egg production; lighting programs